ChemInform Abstract: Nucleophile‐Selective Cross‐Coupling Reactions with Vinyl and Alkynyl Bromides on a Dinucleophilic Aromatic Substrate. Issue 34 (August 2015) - He, Lu‐Ying; Schulz‐Senft, Mathias; Thiedemann, Birk; Linshoeft, Julian; Gates, Paul J.; Staubitz, Anne
Abstract A nucleophile‐selective cross‐coupling reaction of dinucleophilic thiophene (I) with vinyl and alkynyl bromides is developed, extending the scope of electrophiles usable in Sonogashira‐ or Heck‐type coupling reactions.